Assessment Of Prevalence And Risk Factors Of Urinary Tract Infections In Pediatric Diabetic Cases: A Systematic Review (The Review of Diabetic Studies, 2025)
BackgroundUrinary tract infections (UTIs) are among the most common bacterial infections affecting individuals with diabetes mellitus. Pediatric patients with diabetes are particularly vulnerable due to immature immune defenses and metabolic instability. Understanding the prevalence and risk factors for UTIs in this group is crucial for prevention and management.ObjectiveTo systematically review and synthesize current empirical literature on the prevalence, risk factors, microbial patterns, and antibiotic resistance of UTIs among pediatric and adolescent diabetic populations.MethodsThis study followed PRISMA 2020 guidelines for systematic reviews. Databases including PubMed, Scopus, Embase, and Google Scholar were searched for studies published between 2010 and 2025. Eligibility criteria included peer-reviewed studies on UTI prevalence and associated risk factors in pediatric or diabetic populations. Twenty-two studies were included after rigorous screening and quality assessment using the Newcastle-Ottawa Scale and AMSTAR-2.ResultsThe review identified a consistently elevated prevalence of UTIs in diabetic children, with female sex, poor glycemic control, chronic kidney disease, and residual urine volume as key risk factors. A notable rise in antibiotic resistance was observed, particularly among common pathogens such as E. coli. Glycosuria, medication effects (e.g., SGLT2 inhibitors), and structural urinary tract abnormalities further increased susceptibility.ConclusionPediatric patients with diabetes are at significantly elevated risk for UTIs, requiring targeted diagnostic protocols and tailored antimicrobial strategies. Early identification of high-risk individuals, especially females and those with poor metabolic control, can reduce complications. Further pediatric-specific longitudinal research is warranted.